Guidelines for Pomegranate Nutrient Management in Florida - Shinsuke Agehara; Weining Wang; Ali Sarkhosh (EDIS, 2019)
Many Florida growers are interested in the potential of pomegranate as an alternative fruit crop. The first flush of flowers produces the best quality fruit, and climatic conditions have a great impact on the timing of flowering. Proper fertilization is critical to promote healthy canopy development, minimize nutrient disorders, and maximize fruit yield and quality. This new 5-page article, written by Shinsuke Agehara, Weining Wang, and Ali Sarkhosh and published by the UF/IFAS Horticultural Sciences Department, provides guidelines for pomegranate nutrient management in Florida. https://edis.ifas.ufl.edu/hs1347